PENGARUH SUBSTRAT YANG BERBEDA TERHADAP PEMIJAHAN IKAN MAS KOKI ORANDA (Carrasius auratus Linnaeus) - Khairani Laila; Junita Purwasih (JURNAL PIONIR, 2020)
This research aims to determine the influence of kind subtrates use that can affect the amount of fecundity of the chef Oranda (Carassius auratus Linnaeus), as well as to know the influence of different substrates on the power of egg incubator and continuity Live the larva of the Goldfish Chef Oranda (Carassius auratus Linnaeus). The research was conducted in July in the water cultivation Laboratory of the Faculty of Agriculture University of Asahan. This study uses a Completely Randomized Design (CRD) with 5 treatment and 5 repetitions. The treatments in this study include A1 (Eichornia crassipes), A2 (Salvinia molesta), A3 (Pistia stratiotes), A4 (fiber-palm), and A5 (Rafia rope). From the results of the study obtained that the highest Fekundity there is the treatment A1 (Eichornia crassipes) with the amount of 3420 eggs. The highest incubator power is at the treatment of A1 (Eichornia crassipes) which reaches 71,86%. And the survival rate of the highest larva is at the treatment of A1 (Eichornia crassipes) by 79,79%. Keywords: Carrasius auratus Linnaeus, Substrate, Fecundity, Hatching Rate, Survival Rate